The Economic Impact of Russia’s Ukraine Conflict on the EU Fuel Markets - Kalogiannidis, Stavros; Chatzitheodoridis, Fotios; Kalfas, Dimitrios; Kontsas, Stamatis; Toska , Ermelinda (International Journal of Energy Economics and Policy, 2022)
The recent Russian invasion of Ukraine has had significant effects on the global economy. The purpose of study is to display how Russia's aggression and the international sanctions imposed have affected the European economy, especially the petrol and gas market. Albeit the goal of sanctions was to press and hurt Russia, seems to harm in equal to the European economies mainly through immediate effects on the supply of energy. If the war in Ukraine lasts, estimated that the energy prices will stay high, and the European governments will feel uncertain about the available quantity and adequacy of energy resources.